Effect of Seaweed (Eucheuma cottonii) Flour Addition on the Level of Preference of Choux Pastry - Fajrianto, Fiqri; Junianto; Maulina, Ine; Rostini, Iis (Aquaculture Department, University of Mataram, 2025)
Choux pastry is a baked product that generally has low fiber content due to its primary ingredient, wheat flour, which contains minimal dietary fiber. Incorporating alternative ingredients rich in fiber can enhance its nutritional value. One such ingredient is Eucheuma cottonii seaweed flour, which is high in dietary fiber and offers potential for innovation in the utilization of fishery-based products. Dietary fiber plays an important role in binding water, improving digestion, and reducing the risk of certain diseases such as cancer. This research aimed to determine the optimal level of Eucheuma cottonii seaweed flour addition to choux pastry based on consumer preference. The study was conducted in December 2024 at the Fishery Product Technology Laboratory, Faculty of Fisheries and Marine Sciences, and at the Chemistry Application Laboratory and PPBS Service Building, Faculty of Mathematics and Natural Sciences, Padjadjaran University. An experimental method was used with four treatments: 0% (control), 7.5%, 10%, and 12.5% seaweed flour. Organoleptic tests (appearance, aroma, taste, and texture) were performed by 25 semi-trained panelists, and proximate analysis was conducted. The results showed that the choux pastry with 10% seaweed flour was the most preferred, with organoleptic scores of 7.8 for appearance, 7.6 for aroma, 7.5 for texture, and 7.7 for taste. Proximate analysis indicated that the 10% seaweed flour choux pastry contained 0.3% crude fiber, 2.9% moisture, 2.28% ash, 27.43% fat, 11.27% protein, and 56.09% carbohydrates.